The Influence of Change Management, Organizational Culture and Transformational Leadership on the Performance of Indonesian Sharia Bank Employees - Qonitah Qonitah; Muhammad Sholahuddin (Brilliant International Journal Of Management And Tourism, 2024)
Performance is important for a company or organization to support progress and achieve the organization's vision and mission. Many factors and variables can influence employee performance. The purpose of this study is to analyze the effect of change management, organizational culture, and transformational leadership on the employee performance of Bank Syariah Indonesia. This research fills the research gap and requires repeated testing to assess the impact of change management and organizational culture with transformational leadership on employee performance from different perspectives. This empirical study research uses sampling techniques using non-probability sampling of 100 respondents for all employees of Bank Syariah Indonesia Solo Branch. Multiple linear regression analysis data processing techniques reveal that Change Management and Organizational Culture variables influence Transformational Leadership. While Change Management does not influence employee performance, Transformational Leadership and Organizational Culture influence employee performance. The results of this analysis provide a very important picture of the leader's role in empowering and encouraging workers through active involvement with them, in addition to visualizing positive organizational principles that can improve organizational performance.